Numerical software verification : 10th International Workshop, NSV 2017, Heidelberg, Germany, July 22-23, 2017, Proceedings /: 10th International Workshop, NSV 2017, Heidelberg, Germany, July 22-23, 2017, Proceedings. (2017) - Unknown
No abstract available